## Monday, January 6, 2014

### Solutions to Residue Problems:

1) Find the residue for f(z) =  3 exp (z)/  z 4

We know from the residue formula:

Res f(z) = c - 1

= 1/ (m – 1)!  lim z ® a    d m - 1   / dz m - 1    {(z – a k) m    f(z) }

The pole is of order m = 4 at z = 0, then:

Res f(z) = 1/ 3!  lim z ® 0      d 3   / dz3    {(z -  0) 4     ×  3 exp (z) / z 4  }

Res f(z) = 1/ 3!  lim z ® 0     d 3   / dz 3   { 3exp (z)}

Res f(z) = 1/6   lim z ® 0     { 3exp (z)} = 3/6  = ½

2) Find Res f(z) for cos z/ z 5

From the residue formula:      Res f(z) = c - 1

= 1/  (m – 1)!  lim z ® a      d m - 1   / dz m - 1    {(z – a k) m    f(z) }

The pole is of order m = 5 at z = 0  so that:

Res f(z) = 1/ 4!  lim z ® 0      d 4   / dz4    {(z -  0) 5     ×  cos (z) / z 5 }

Res f(z) = 1/ 4!  lim z ® 0     d 4   / dz 4   { cos  (z)}

Taking the 4th derivative of cos z:

1) d/ dz (cos z) = - sin z and 2)  d/dz (-sin z) = - cos z

3) d/dz (- cos z) = - (-sin z) = sin z and  (4) d/dz (sin z) = cos z

Therefore:

Res f(z) =  1/ 4!  lim z ® 0   (cos z) =  1/24 (1) = 1/ 24

3) Find all the residues at those singular points inside the circle  ÷ z  ÷     =    2

For:  f(z) =   z 2   / ( z 4  - 1)

Rewrite f(z):

z 2  / ( z 4  - 1)  =    z 2   / ( z 2  - 1) ( z 2  +  1)

Look at factors of the denominator:

( z 2  +  1)  =   (z + i)  (z – i)

( z 2  - 1)    =   (z + 1) (z – 1)

Then rewrite f(z) again:

z 2 / ( z 4  - 1)  =    =    z 2   / ( z  - 1) ( z  +  1) (z + i)  (z – i)

The order of the poles is simple, i.e.  m = 1  and 4 singular points occur inside the circle  ÷ z  ÷   =   2

z= 1, z = -1, z = i, z = -i

Look at z = 1:

Res (f(z)) =  (z – a)     f(z)  =

lim z ® 1   (z – 1)   [z 2  / ( z  - 1) ( z  +  1) (z + i)  (z – i)]

Res (f(z)) =  lim z ® 1   [z 2   / ( z  +  1) (z + i)  (z – i) ] =

z 2 / 4 z 3  ÷ z = 1   = 1 / 4(1) 3   =  ¼

Note: by L’Hospital’s rule:

Res [f, zo] =  lim z ® z o   1 / ( z 4  - 1)  =

lim z ® z o   1  / 4 z 3     =  ( 1/ 4 zo 3  )

Proceeding, for z = -1:

Res (f(z)) =  lim z ®  -1   [z 2   / ( z  -  1) (z + i)  (z – i)] =

z 2 / 4 z 3 ÷  z =- 1      = (-1)  / 4(-1) 3 =  - ¼

Similarly, for z = -i:

Res (f(z)) =  lim z ®  -i   [z 2  / ( z  -  1) (z + 1)  (z – i) ]

=  z 2 / 4 z ÷  z =- -i   =  (-i) 2 / 4(-i) 3 =  -1/ 4i =  1/ 4i =  -i/ -4 = i/4

Similarly, for z = i:

Res (f(z)) =  lim z ®  i   [z 2  / ( z  -  1) (z + 1)  (z + i)

=    z 2 / 4 z 3 ÷  z = i  =  (i) 2 / 4(i) 3 =  -1/ -4i =  1/ 4i =  -i/ 4